Improving the efficiency of enterprise procurement logistics in the digitalized economy - Jian, Liu (Харківський національний автомобільно-дорожній університет, 2024)
The theoretical foundations of procurement logistics of wholesale trade enterprises are defined; the role and place of wholesale trade enterprises in supply chains are analyzed; the relationship of wholesale trade enterprises with contractors in the organization of procurement logistics is considered; the peculiarities of using modern information systems implemented in the procurement activities of wholesale trade enterprises are determined; the wholesale trade market for the HoReCa segment is researched; proposals and recommendations for improving the procurement logistics are developed.
Keywords: trade; kanban system; wholesale trade; inquiry system; retail trade; trade and manufacturing trade; distributor; dealer; international trade; business partnership